Analisis Mengenali Minat Bakat Siswa SMKN 1 Setia Janji Menurut Teknik Certainty Factor - Rian Bariadi; Guntur Maha Putra; Rohminatin Rohminatin (J-Com (Journal of Computer), 2022)
Abstract: SMKN 1 Setia Janji is one of the State Vocational Schools in Urung Pane, Kec. Faithful Promise, Kab. Asahan, North Sumatra. The determination of the research location at SMKN 1 Setia Janji is due to the lack of facilities to support students in determining the interests and talents that exist in the students themselves, especially in extracurricular support facilities so as to create a lack of students in finding interests and talents within students. Therefore, this study aims to design an expert system application using Certainty Factor which is intended to provide convenience for students in choosing the right extracurricular according to the interests and talents that exist in the student. This application is designed using the PHP programming language model and the system database uses MySQL. Methods The research uses descriptive qualitative methods and tends to use analysis. The final results obtained in the existing data sample show that student interest in Mading Extracurricular has a percentage of 86.9% and Paskibraka Extracurricular has a percentage of 80.8%, so that the data will be used as a student's choice in determining extracurricular activities at school. Keywords: extracurricular; certainty factor; PHP; MySQL Abstrak: SMKN 1 Setia janji ini merrupakan slah satu SMKN yang ada di Urung Pane, Kec. Setia Janji, Kab. Asahan, Sumatera Utara. Penetapan lokasi penelitian di SMKN 1 Setia janji ini dikarenakan masih minimnya fasilitas untuk mendukung para siswa dalam menentukan minat dan bakat yang ada pada diri siswa itu sendri terutama dalam fasilitas pendukung ekstrakulikuler sehingga membuat kurangnya siswa dalam menemukan minat dan bakat didalam diri siswa. Maka dari itu Penelitian ini bertujuan untuk merancang sebuah aplikasi Sistem Pakar dengan menggunakan Certainty Factor yang ditujukan untuk memberikan kemudahan bagi  siswa dalam memilih ekstrakurikuler yang tepat sesuai minat dan bakat yang ada pada diri siswa tersebut. Aplikasi ini dirancang menggunakan Model bahasa pemograman PHP dan database sistem menggunakan MySQL. Metode Penelitian menggunakan metode kualitatif yang bersifat deskriptif dan cenderung menggunakan analisis. Hasil akhir yang di dapat dalam sample data yang ada menunjukan bahwa minat siswa tentang Ekstrakurikuler Mading memiliki persentasi sebesar 86.9 % dan Ekstrakulikuler Paskibraka memiliki persentasi sebesar 80.8 %, sehingga data tersebut akan bisa di gunakan sebagai pilihan siswa dalam menentukan Ekstrakurikuler di sekolah. Kata Kunci : ekstrakurikuler; certainty factor; PHP; MySQL.